Iodine-induced stress corrosion cracking behavior of alloy ZIRLO with Zr coatings by electrodepositing with different pulse current densities. (December 2021) - Li, Yusha; Liu, Yanhong; Li, Guangbin; Dong, Xiaoxu; Wang, Ying; Gu, Zongxing; Zhang, Yingchun
Abstract: To improve the iodine-induced stress corrosion cracking(I-SCC) resistance of alloy ZIRLO used as nuclear fuel cladding in light water reactor, Zr coatings were prepared on ZIRLO with different current densities by pulse electrodeposition (PED) method. I-SCC behavior of the Zr-coated alloy ZIRLO was tested by slow strain rate tensile (SSRT). The results revealed that the I-SCC resistance of alloy ZIRLO was enhanced by Zr coatings. I-SCC susceptibility indices of ultimate tensile strength and failure time were reduced from 0.23 to 0.12 and 0.55 to 0.40, respectively. Zr coatings with columnar crystals could suppress pitting generation and reduce the diffusion rate of iodine perpendicular to the surface from 3.258 × 10 −12 m 2 /s to 0.175 × 10 −12 m 2 /s. The sample with Zr coating obtained under the current density of 90 mA/cm 2 had the highest ultimate tensile strength and ductility, which is attributed to the high interfacial adhesion strength and the structure of continuous columnar crystal. Highlights: The Zr coating was electrodeposited on alloy ZIRLO as the I-SCC resistance layer for the first time. It was confirmed that the I-SCC resistance of alloy ZIRLO was enhanced by Zr coatings. The I-SCC susceptibility indices of UTS and tf were reduced from 0.23 to 0.12 and 0.55 to 0.40, respectively. The mechanism of I-SCC resistance was revealed, and it suggested that Zr coatings could suppress pitting generation. Zr coatings with columnar crystals could reduce the diffusion rate of iodine from 3.258 × 10 −12 m 2 /s to 175 × 10 −12 m 2 /s.